Light physical activity increased body fat percentage in elderly Javanese - Fatmah, Fatmah; Nasution, Yusran (Universa Medicina, 2011)
The prevalence of obesity in Indonesia is rapidly increasing, particularly in older people. Obesity is characterized by increased percentage of body fat in the form of visceral fat and non-visceral or subcutaneous fat. The aim of this study was to analyze body fat percentage (BFP) and associated risk factors, i.e. type of residence (rural or urban), physical activity, gender, age, intakes of energy and fat, and socio-economic background (educational level and occupational status). This cross-sectional study was conducted on 812 older persons (517 females and 295 males) from December 2007- February 2008 in the cities of Surabaya, Semarang, Yogyakarta, Wonogiri, Gunung Kidul, and Magetan subdistricts. BFP was assessed using an Omron Fat Analyzer. Nutritional intakes were collected through interviews using semi-quantitative food frequency questionnaire (FFQ). To obtain overall total energy expenditure for physical activity (PA), the energy expenditures for exercise (sports) PA, daily activities, and leisure time PA were added together. The study results indicated that urban residence and light PA at age 55 years constituted risk factors for high BFP. Light PA at 55 years of age was the most influential risk factor, since it was 4.3 times greater than vigorous PA at the same age (OR=4.3; 95% Confidence interval 2.6-7.1) It is recommended to implement nutritional counseling about adequate intakes for increased PA in all age groups (adolescents, adults, older persons), particularly in urban areas with their greater risk of high BFP.